Pandangan Kiai Madura Terhadap Pembayaran Non Tunai - Anna Zakiyah Hastriana (Institut Ilmu Keislaman Annuqayah, 2017)
Banking services are needed by the majority of society to facilitate all of their economic activities, especially to help their business or business development. One of the services performed by the banks, both conventional and sharia banks in accordance with the declaration of the BI program is a non-cash payment, better known as GNNT (Non-Cash National Movement). GNNT is one way to make a country more advanced. The indication of community acceptance to non-cash payment is the use of sophisticated technology, mindset and lifestyle of the society.Therefore, this paper examines Madura kiai's view to the program. Due to its social condition, the kiai's views on banking services are polarized. On the other hand, a kiai is a central figure who has a great influence on the environment of his society. The view of the madura kiai is divided into two: against non-cash payments in conventional banks and sharia banks. The non-cash payment to a conventional bank, the kiai's views are divided into three: halal, haram and syubhat. While in sharia banks, the views of kiai are divided into two: halal and syubhat. The polarization of views is in line with the polarization of the kiai type, between the salafiyah kiai and the inclusive kiai. But in general, the kiai give a positive response on the establishment of sharia banks.